THE VARIETY OF ANTHROPOGENIC LANDSCAPE AND THE SCIENTIFIC THEORETICAL BASIS OF THEIR CLASSIFICATION - Nazarov Maksud Geldiyorovich (Journals Park Publishing, 2023)
The article analyzes the doctrine of anthropogenic landscapes and their theoretical foundations, as well as their scientific and practical significance through the classification of anthropogenic landscapes.
Keywords: Landscape, natural resource, gene pool, geosystem, natural anthropogenic landscape, anthropogenic landscape, cultural landscape.